2023
DOI: 10.1126/science.adg5725
|View full text |Cite
|
Sign up to set email alerts
|

Ecology-relevant bacteria drive the evolution of host antimicrobial peptides in Drosophila

Abstract: Antimicrobial peptides are host-encoded immune effectors that combat pathogens and shape the microbiome in plants and animals. However, little is known about how the host antimicrobial peptide repertoire is adapted to its microbiome. Here, we characterized the function and evolution of the Diptericin antimicrobial peptide family of Diptera. Using mutations affecting the two Diptericins ( Dpt ) of Drosophila melanogaster … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 80 publications
1
31
0
Order By: Relevance
“…Indeed, pioneering studies in innate immunity revealed that, although Toll signalling to NF-κB is conserved between insects and mammals, Toll functions as a cytokine receptor in Drosophila, unlike Toll-like receptors, which function as PRRs [80][81][82][83]. Furthermore, recent studies indicate that the antimicrobial peptides regulated by NF-κB in different Drosophila species are subjected to diversification and specialization driven by differences in the ecologies of the flies [84].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pioneering studies in innate immunity revealed that, although Toll signalling to NF-κB is conserved between insects and mammals, Toll functions as a cytokine receptor in Drosophila, unlike Toll-like receptors, which function as PRRs [80][81][82][83]. Furthermore, recent studies indicate that the antimicrobial peptides regulated by NF-κB in different Drosophila species are subjected to diversification and specialization driven by differences in the ecologies of the flies [84].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also substantial variation in susceptibility just among species with the "S" allele, suggesting this Diptericin allele is not the sole driver of the patterns observed here. Further study across a broader range of species that vary in their Diptericin alleles are required, perhaps combined with measurements of the speed of induction of Diptericin and other AMPs, given rapid induction has been demonstrated to be important for host survival [34,35,49].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the compartmentalization of immunerelated genes and fine-tuning of AMP expression in the different parts of the gut of the oriental fruit fly Bactrocera dorsalis results in the separation of diverse niches that favour the cultivation of beneficial microbes [15]. Additionally, it was demonstrated in Drosophila that gene duplication and sequence convergence of the AMPs Diptericins could evolve diverse functions, resulting in a species-specific AMP repertoire needed for adaptation to the occupied ecological niche and its associated microbial community [16,17].…”
Section: Introductionmentioning
confidence: 99%